Electromagnetic Waves in Complex Systems Selected Theoretical and Applied Problems - Sirenko, Yuriy; Velychko, Lyudmyla (Springer Series on Atomic, Optical, and Plasma Physics,, 2016)
This book gives guidance to solve problems in electromagnetics, providing both examples of solving serious research problems as well as the original results to encourage further investigations. The book contains seven chapters on various aspects of resonant wave scattering, each solving one original problem. All of them are unified by the authors' desire to show advantages of rigorous approaches at all stages, from the formulation of a problem and the selection of a method to the interpretation of results. The book reveals a range of problems associated with wave propagation and scattering in natural and artificial environments or with the design of antennas elements. The authors invoke both theoretical (analytical and numerical) and experimental techniques for handling the problems. Attention is given to mathematical simulations, computational efficiency, and physical interpretation of the experimental results. The book is written for students, graduate students and young researchers. .